Structural design of responsive under-deck cable-stayed footbridges. (July 2022) - Corral, María del Mar; Todisco, Leonardo
Abstract: The use of prestressing through external tendons has been extensively adopted in bridges to optimize the internal stress distribution. The contribution in withstanding permanent and live loads depends on the initial stressing and the relative stiffness between the deck and the tendons. However, these configurations only allow an optimal structural behaviour for a specific load distribution. This paper proposes to extend this ideal behaviour for any loading condition, using a responsive system which gradually modifies the tension in the cables as the live load increases. The responsive system is applied to a footbridge, where the adaptive behavior is materialized through a linear actuator located between the deck and the under-deck cable-stayed system. This study presents analytical and numerical analyses to shed light on the structural design of these systems. Considering a variable degree of responsiveness, it is possible to quantify the benefits of the responsive system. Furthermore, several parametric analyses are carried out to identify the optimal solution in terms of material savings. In addition, it is verified that fatigue in cables, vibrations and the eventual shutdown of the actuator do not compromise the structural performance of the system. Results show that a relevant material reduction can be achieved using partially responsive systems. Specifically, the slenderness of the structure can almost be doubled if compared to the same system without any responsive behaviour.